Pain control due to botulinum toxin therapy in cervical dystonia relates to the sensorimotor integration process - Aparna Wagle Shukla; Robert Chen; Wei Hu (Dystonia, 2023)
Background: Botulinum toxin (BoNT) injections have been found to improve pain symptoms of isolated cervical dystonia (CD). In addition to muscle relaxation at the peripheral level, few studies suggest that BoNT has effects on the central brain circuitries. The effects of BoNT on central circuitries that may be pain-related have not been examined. We probed these central effects with transcranial magnetic stimulation (TMS) techniques in a CD cohort presenting with significant pain.Methods: TMS-based measures of sensorimotor integration that are mediated through central processes, such as the short and long latency afferent inhibition (SAI and LAI) and measures for motor cortical excitability including short-interval intracortical inhibition (SICI) and intracortical facilitation (ICF) were recorded. These measures were recorded at specific interstimulus intervals (ISI) using paired-pulse paradigms before and after the peak effects of BoNT injections. Normative TMS data from age-matched healthy controls were collected for comparisons. Clinical pain symptoms were recorded with Toronto Western spasmodic rating scale (TWSTRS)-pain and a visual analog scale (VAS).Results: Eleven CD subjects (mean age ±SD, 53.1 ± 6.3 years) and 10 age-matched healthy controls were enrolled. SAI was found to be increased in CD patients at baseline, however at the time of peak BoNT effects, it revealed a significant change with normalization to healthy control data (SAI ISI 20 ms, p = 0.001; SAI ISI 30 ms, p = 0.03). The change in SAI correlated with improvements in pain levels assessed with TWSTRS-pain and VAS and the total dose of BoNT injected (corrected for multiple correlations). LAI, SICI, and ICF measures were similar to the healthy controls and remained unchanged with BoNT therapy.Conclusion: Pain control in CD from BoNT therapy relates to modulation of sensorimotor integration at the cortical level.